Perfusion strategy and mid-term results of 58 consecutive pulmonary endarterectomy. (September 2019) - Yan, Shujie; Lou, Song; Zhu, Jiade; Liu, Sheng; Zhao, Yu; Song, Yunhu; Wang, Hui; Ji, Bingyang
Objective: The aim of this retrospective study was to review and report short-term and mid-term outcomes of pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension at our institute in the recent 2 years and to describe perfusion strategy. Methods: A total of 58 consecutive patients with chronic thromboembolic pulmonary hypertension underwent pulmonary endarterectomy under deep hypothermia circulatory arrest with an established perfusion practice between November 2015 and December 2017. Peri-operative data and patients' outcome were retrospectively analyzed. Results: Mean pulmonary artery pressure was decreased (49 (40-56) mmHg vs 27 (20-31) mmHg, p < 0.001), and pulmonary vascular resistance (724 (538-1108) vs 206 (141-284) dyn second cm −5, p < 0.001) improved significantly after surgery. In-hospital mortality was 1.7% and postoperative complication rate was 27.6%. Antipsychotic medication of olanzapine was prescribed for 36 patients (62.1%), which was independently related to total deep hypothermic circulatory arrest time, postoperative blood potassium concentration, and hematocrit. The majority of patients recovered uneventfully with good mid-term cardiac function (New York Heart Association I-II: 98.1%) and neurological outcome (Glasgow Outcome Scale—Extended Upper Good Recovery: 74.1% and Lower Good Recovery: 20.3%). Mid-term neurological outcome was associated with post–pulmonary endarterectomy antipsychotic medication. Conclusion: Short-term and mid-term outcome after pulmonary endarterectomy was comparable to high-volume centers. Incidence of post–pulmonary endarterectomy delirium was relatively high and associated with mid-term neurological outcome. Total deep hypothermic circulatory arrest time, postoperative blood potassium concentration, and hematocrit were independent risk factors of postoperative olanzapine medication. More efforts and further research are required to optimize the neuroprotection of perfusion practice.